The effect of tree induced suction on slope stability analysis - Muhammad Farhan, Zolkepli (2022)
Nowadays, many problems regarding slope failure happened due to cutting down of vegetation. The existence of tree on top of slope is very important to increase soil slope stability. This study explore the influence of active root tree zone (Alstonia Angustiloba) located on top of a slope to reduce soil moisture content thus increase the shear strength of soil slope. Soil matric suction generated at the vicinity of the slope due to tree water uptake is the main focus of this study since it will influence the factor of safety (FOS) of slope. This research employed several approaches i.e field monitoring work for soil suction and rainfall collection, laboratory works for soil classification and determining the shear strength parameters of the soil, subsurface investigation using electrical resistivity imaging (ERI), digital mapping using unmanned aerial vehicle (UAV) and verification of actual soil suction pattern with numerical modelling. Field monitoring works were carried out to obtain soil suction data at the selected slope with two conditions (without and with tree on top of the slope). The unsaturated shear strength behaviour under different stress level was investigated, by conducting consolidated isotropic undrained (CIU) test by replicating the actual matric suction monitored at the study area. From this suction pattern, it was proven that the majority of suction changes were greater at the proximity of the tree trunk (1.1 m) and at a shallow depth of 0.25 m. In addition, Electrical Resistivity Imaging (ERI) was conducted on two layouts (horizontal and vertical) of the slope to obtain the subsurface images of the slope. This ERI survey applies two protocols known as Wenner protocol and Schlumberger protocol. These images from ERI were compared to unsaturated soil suction contour generated using GiD software. This study also implement modern methods for soil slope mapping by using unmanned aerial vehicle (UAV). The findings also applied the safety values (FOS) on 18th February 2018 and 22nd February 2018 into the map to study the daily stability values of the slope and considered as the main novelty of this study. Finally, numerical simulation modelling was applied based on the laboratory results to obtain most appropriate condition to replicate tree water uptake within soil slope during dry period. The factor of safety (FOS) of soil slope in 19th February 2018 with tree on top of it reached up to 53 % higher compare to slope without tree. From the results of comparison between suction contour and ERI contour, soil suction contour proved to be more suitable in term of stability analysis, while the ERI contour is more suitable to detect underlying materials underneath the soil based on the ability of materials to resist or allow electric current flow. This study verified the finding from ERI survey with the soil properties of Pahang Matriculation College. ERI prove the existence of clay in the soil which verified the high clay contents (22.8 %) in the soil itself. Finally, an acceptable agreement has been achieved between simulation of numerical modelling and actual suction collected from field monitoring work with a small difference of 5 % only. This research proved high influenced of single tree on top of soil slope to increase soil slope stability by decreasing the existence moisture in the soil itself.